Constructing biology education research identities: a duoethnography - Sung, Rou-Jia; Holt, Emily A.; Lo, Stanley M. (Frontiers in Education, 2023)
An emerging theme that has gained traction across science, technology, engineering, and mathematics (STEM) classrooms in recent decades is acknowledging who is responsible for the discoveries and content that we teach. Centering the human aspect of who the researchers are and how their identities intersect with perspectives in research impacts the lens through which the work is done but also shapes the community of practice in our classrooms and the evolving ecosystem of research communities that contribute to STEM education. In particular, discipline-based education research (DBER) is an emerging interdisciplinary field aimed at understanding and improving discipline-specific learning and teaching. Entering and establishing oneself in a new research field can be a daunting process. For many DBER scholars who began their careers in another discipline, their career trajectories have necessitated this challenge. Here, we focus on our experiences in Biology Education Research (BER). We use duoethnography to explore our overlapping trajectories into and engagements with BER, allowing for the juxtaposition of our experiences to give meanings to and build new understandings of our pathways in BER, which include entry points, reasons for persistence, and identity navigation. Through collaborative reflections, we formulated novel insights that we experienced BER as a community of practice that values the participation of emerging scholars and arrived at a transformed understanding that our educator identities were important driving factors for our continuing pursuit of BER. Results from this duoethnography not only provide insights into how BER faculty may navigate multiple professional identities but can also shed light on potential opportunities and challenges for research and practice partnerships connecting science and education faculty where such identities reside not in single individuals but with multiple persons in a cross-disciplinary collaboration. We see parallels between this work considering faculty identity and pathways into BER with work considering student identity and pathways into STEM, and we hope that these results also highlight the value of utilizing qualitative methodologies that may be novel to both the BER and more broadly, DBER, communities as a tool for centering the human experience that can spark future work and applications within STEM education.